Helping poor farmers to help themselves: Evidence from a group-based aid project in Mozambique - Milla Nyyssölä; Jukka Pirttilä; Susanna Sandström (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper evaluates the impact of an integrated rural development programme on farming techniques and food security in the Gaza area of rural Mozambique. We examine the impact of a group-based approach, in a country with few impact evaluations of technology adoption in farming. Using self-collected panel data on over 200 households from treatment and control villages from 2008-10, we examine the impact of the aid programme on people living in the treatment villages, using the difference-in-differences approach, and on those who participate in the farmers' groups, using instrumental variables techniques. The results on farming activities and food security indicate some positive immediate impacts on technology adoption and self-reported food security.
Keywords: O1; O2; 330; food security; farming techniques; fertilizer use; technology adoption; impact evaluation; Mozambique; Agrartechnik; Ernährungssicherung; Ländliche Entwicklungsplanung; Selbsthilfeförderung (Entwicklungsländer); Mosambik